Primary school teachers’ assessment for learning practice for students’ learning improvement - Gebremariam, Hailay Tesfay; Gedamu, Abate Demissie (Frontiers in Education, 2023)
Assessment for learning practice and learning improvement are the two vital variables in this study. This article explores primary school teachers’ assessments for learning practices for student learning improvement. Participants were selected through a cluster random sampling technique for a questionnaire survey (n = 242) from primary schools to meet this objective. Fifteen (15) teachers were randomly selected for an in-depth interview, and five informal conversations were selected through purposive sampling. The data acquired through the closed-ended items of the questionnaire were analyzed using quantitative statistical measurements (mean, standard deviation, ANOVA, and post hoc methods). Thematic verbal descriptions were employed to analyze the qualitative data. Primary school teachers, on the other hand, had highly positive classroom environments, moderately positive learning intentions and success, feedback in assessment practices, and self- and peer-assessment practices regarding learning assessment. Although the results from the quantitative data indicated that the primary school teachers had high and moderate assessments for learning practice, the interviews revealed that they had low confidence in learning practice assessments owing to challenges they faced during practice. These challenges relate to transparency, experience, training, school problems, and preference-based reliance.